Voluntary work, demographic, social and economic features and health self-perception by elderly people from Porto Alegre (Brazil) - Souza, Luccas Melo de; Lautert, Liana; Hilleshein, Eunice Fabiani (Revista da Escola de Enfermagem da USP, 2010)
The objective of this cross-sectional, comparative study was to describe the demographic, socioeconomic and health characteristics of elderly voluntary workers of a Non-governmental organization of Porto Alegre, and investigate the influence of voluntary work and the referred characteristics on the subjects' self-perception of health, compared to a paired group of elderly individuals who did not perform any voluntary work. Through interviews it was found that 87.4% of the elderly voluntary workers were women, with complete secondary education, had their own income and followed a religion and a healthy lifestyle. The comparison of data from both groups showed that self-perception of great health was more common among voluntary workers (30.5% compared to 6.1%, p=0.054). Multivariate analysis revealed that performing voluntary work and having fewer diseases influenced the individuals' having a positive self-perception of their health (p